Characterization of proton conducting carboxymethyf celiulose/chitosan dual-blend based biopolymer electrolytes - Mohd Saiful Asmal, R.; Nor Sabirin, M.; Mohd Ikmar Nizam, M.I. (2014)
This article presents the discovery on biopolymer electrolytes comprising of ammonium nitrate, NH4N03 with dual-blend biopolymer materials, carboxymethyl cellulose/chitosan which were prepared via solution-casting technique. The biopolymer blend based electrolyte films were characterized by Fourier Transform Infrared spectroscopy to investigate the formation of the dualblend biopolymer based complexes. X-Ray Diffraction result showed that all dual-blend samples Werepredominantly amorphous. Electrochemical impedance spectroscopy was conducted to obtain their ionic conductivities. The highest conductivity at ambient temperature of 1.03 x 10-5 S cm-l was obtained for the electrolyte film containing 40 wt% of NH4N03. These results indicated that the dual-blend biopolymer based electrolyte has potential for application of electrochemical deVices.